Effectiveness in use of molten pool heat - Dmitrik, V. V.; Shevchenko, V. V. (International Association "Welding", 2001)
Method for estimation of the amount of the arc heat introduced into parent metal and transferred with the liquid metal. Hows from the head to the tail portion of the weld pool is suggested. It is shown that the efficiency in use of the molten pool heat can be increased by using an extra filler metal and selecting the optimum parameters of welding.
Keywords: arc welding; arc heat; welding pool; overheating; heat consumption